1987
DOI: 10.1126/science.3576186
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cones in Human and Monkey Retina: Individual Variability and Radial Asymmetry

Abstract: The distribution of photoreceptors is known for only one complete human retina and for the cardinal meridians only in the macaque monkey retina. Cones can be mapped in computer-reconstructed whole mounts of human and monkey retina. A 2.9-fold range in maximum cone density in the foveas of young adult human eyes may contribute to individual differences in acuity. Cone distribution is radially asymmetrical about the fovea in both species, as previously described for the distribution of retinal ganglion cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
295
4
4

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(335 citation statements)
references
References 16 publications
32
295
4
4
Order By: Relevance
“…The sizes of MH's summation and 1.87 min arc, respectively. Curcio, Sloan, areas were 8 min arc for both fovea and paraPacker, Hendrickson and Kalina's (1987) results fovea. Since both observers had comparably yield center-to-center spacing for the cones of excellent acuity (Methods section), blurring due 0.48 min arc at the fovea centralis and 1.83 min to optical factors is not likely to be the reason arc at 5 deg nasal eccentricity.…”
Section: Discussionmentioning
confidence: 82%
“…The sizes of MH's summation and 1.87 min arc, respectively. Curcio, Sloan, areas were 8 min arc for both fovea and paraPacker, Hendrickson and Kalina's (1987) results fovea. Since both observers had comparably yield center-to-center spacing for the cones of excellent acuity (Methods section), blurring due 0.48 min arc at the fovea centralis and 1.83 min to optical factors is not likely to be the reason arc at 5 deg nasal eccentricity.…”
Section: Discussionmentioning
confidence: 82%
“…Scleral thinning is greatest at the posterior pole of the eye, the anatomical region of greatest retinal photoreceptor density and vital to detailed visual discrimination (5,6). In some individuals, the thinned posterior sclera precipitates local ectasic change or staphyloma (7,8).…”
mentioning
confidence: 99%
“…This distribution of response density approximately corresponds to the anatomical occurrence of cone distribution of the posterior pole. [18][19][20]31 The control group in this study was not age matched, which could have an influence on the results because it is known that an age-related effect exists. Other studies showed a decrease of amplitudes in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…The visual stimulus, consisting of a matrix of hexagonal areas flickering concurrently according to a short m-sequence, is displayed directly onto the retina covering a visual angle of about 121 or a diameter of 241, respectively ( Figure 2). 18,19 It consists of a matrix of 61 hexagonal elements and is generated by a helium-neon laser (632.8 nm) modulated via an acousto-optic modulator. The matrix has been presented according to a scaling factor 1:4, so that the hexagonal size would be accordingly scaled with eccentricity in order to evoke focal responses of approximately the same amplitude per stimulus element in the response arrays of normal individuals.…”
Section: Methodsmentioning
confidence: 99%